CHARACTERISTIC FEATURES OF PARATEXTS IN UKRAINIAN TRANSLATIONS OF THE HOLY SCRIPTURES - Oksana V. Dzera (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The current paper aims to present linguistic, pragmatic, and sociocultural features of the paratexts of the Peresopnytsia Gospel and five complete Ukrainian translations of the Holy Scriptures. The ultimate goal of the study is to highlight the peritextual and epitextual dimensions of these translations and to classify translation paratexts, whose characteristics are determined by both the translator’s strategy and the mono-confessional or interconfessional requirements of translation commissioners. The article’s assumptions are grounded in the interdisciplinary approach at the interface of translation studies, biblical studies, religious studies, and historiography. The objective of developing a classification of paratexts in Bible translations within historical, theoretical, and critical contexts is accomplished via the methods of analysis, synthesis, induction, and modelling. The interpretive textual and cultural analysis methods are applied to identify and explain cultural, national, and religiously determined connotations of the paratexts. The comparative translation analysis provides a historically based translation quality assessment. As a result, paratexts of Ukrainian Bible translations have been classified according to thematic and pragmatic criteria. The paratextual dimensions of Bible translation are marked with 1) blurred agency (in many cases, it is difficult to determine the contribution of the translator or theological and literary editors), 2) restrictive requirements of the commissioner, 3) the impact of the overall translation strategy on the nature, type, and content of paratexts. However, no restrictions can conceal the implicit reader of each of these translations, to whom the paratexts appeal as a “second voice” of the main text. Paratexts of the first partial Ukrainian translations of the Holy Scriptures of the Confessionalism period (second half of the 16th century) are characterised by didacticism and a mono-confessional political orientation. The most important translation of that time, the Peresopnytsia Gospel, is analysed to specify the following types of verbal paratexts: 1) identification, containing data on the commissioner/publisher and the translators, as well as the date and place of its creation; 2) informative, providing all additional information not found in the prototext, including brief paraphrases of the main text, dates of the church calendar, and information on the structure of the book; they are often mono-confessional and polemical; 3) meta-lingual, explaining Church Slavonic vocabulary in glosses with Ukrainian equivalents or providing Ukrainian synonyms for Ukrainian words. The findings of the study prove that all complete translations of the Holy Scriptures into Ukrainian, both at the textual and paratextual levels, adhered to the principles of interconfessionality, accessibility for all Christians, and “functional loyalty”. The footnotes were the most important paratexts of the Ukrainian Bible translations made under the auspices of Bible Societies. Only in translations of the Bible of the 21st century does a preface appear, either a short one with general information about the translation strategy (Modern Translation, 2020) or a lengthy one with a detailed justification for the choice of the prototext’s language, a comparative table of the canons of the Old and New Testaments in different translations, and general information about the content of the Bible (New Translation, 2011). The footnotes in all Ukrainian translations done under the auspices of Bible Societies are divided into: explanations of biblical metaphor; explanations of the etymology of proper names; explanations of biblical traditions; alternative readings; foreign language equivalents; and meta-lingual explanations. The prevalence and peculiarities of footnotes depend upon the translation strategy. Thus, only among the footnotes in Ohiyenko’s translation can we trace such types as literal translations of complicated biblical metaphors and explanations of etymological wordplay. In addition, explanations of biblical metaphors are quantitatively prevalent in this translation. Such paratextual features are explained by the principle of foreignization, on which this translation is based. The Modern Translation by R. Turkoniak, in tandem with the Revising Committee of the Ukrainian Bible Society, aims to bring the Scriptures closer to the modern believer, not least through its footnotes. While Ohiyenko’s footnotes offer an alternative reading of some verses in “sacred” languages (Latin, Greek, and Church Slavonic), Turkoniak provides equivalents from translations into modern European languages and previous Ukrainian translations. The elements of “modernization” in the footnotes include vernacular vocabulary and associations with the realities and values of today. The interconfessional nature of Ukrainian translations of the Bible becomes visible in the church affiliations of the agents, such as the tandem of Orthodox Kulish and Greek Catholic Puluj, the cooperation of Ohiyenko, the Metropolitan of the Ukrainian Autocephalous Orthodox Church and Protestant pastors Kuziv and Zhabko-Potapovych, the New (2011) and Modern (2020) translations as part of the project of the Ukrainian Bible Society, which brought together representatives of all denominations of independent Ukraine.